Topology Synthesis for In-Situ Machining Mechanism With Dual Platforms and Decoupled Motions of Position and Rotation - Yang Qi; Jinhan Yang; Xinran Tong (IEEE Access)
To satisfy the complex surface machining requirement for the high attitude adjustment capability of the in-situ machining mechanism, this paper carries out the topology synthesis of the mechanism with dual platforms and decoupled motions of position and rotation, which allows translational positioning and precise attitude adjustment afterward. Firstly, to achieve spatial localization followed by precise attitude adjustment, the concept of a dual-platform system is introduced. The two platforms are designed to perform distinct motion tasks, and the decoupling principle of the dual-platform system based on Finite Instantaneous Screw (FIS) theory is investigated. Secondly, the continuous motion of the in-situ machining task is described using the simplest mathematical expressions, and the finite motion of the mechanism is derived. Thirdly, a topology synthesis method for in-situ machining of parallel mechanisms based on the decoupling principle is proposed. This method integrates the feasible limb structures of positioning and rotation mechanisms and identifies all limbs that satisfy the conditions. Finally, considering the practical requirements of in-situ machining of large components, the assembly conditions for the positioning and rotation mechanisms are established, the principles of connection between the two platforms are discussed and a decoupled connection between the two platforms is achieved. This paper provides a detailed description of the topological synthesis process for a dual-platform in-situ machining mechanism with decoupling of position and rotation. The decoupling principle of the dual-platform is explored, and the topological synthesis procedure for decoupling is presented. A novel topological structure of a dual-platform in-situ machining mechanism is successfully obtained, laying a solid foundation for subsequent kinematic analysis and performance evaluation.